Kinetic analysis of drug–protein interactions by affinity chromatography. (October 2015) - Bi, Cong; Beeram, Sandya; Li, Zhao; Zheng, Xiwei; Hage, David S.
Graphical abstract: Abstract : Information on the kinetics of drug–protein interactions is of crucial importance in drug discovery and development. Several methods based on affinity chromatography have been developed in recent years to examine the association and dissociation rates of these processes. These techniques include band-broadening measurements, the peak decay method, peak fitting methods, the split-peak method, and free fraction analysis. This review will examine the general principles and applications of these approaches and discuss their use in the characterization, screening and analysis of drug–protein interactions in the body.